2022
DOI: 10.47743/pesd2022161003
|View full text |Cite
|
Sign up to set email alerts
|

Charging plastic bags within the demarketing: measuring the environmental attitude and environmental behaviour in Denizli: a structural equality model

Abstract: Plastic bags have either been charged or banned in more than 60 countries around the world. Charging for plastic bags as demarketing practice in Turkey is quite new. The aim of this study is to reveal the relationship among attitude toward reducing the use of plastic bags, environmental attitude and environmental behavior within the framework of the law ratified on January 1, 2019. In order to classify consumers, two dimensions of environmental attitude; ecocentric attitude and anthropocentric attitude were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
1
5
0
1
Order By: Relevance
“…It is crucial to acknowledge that desired outcomes from plastic bags' usage reduction can only be achieved when consumers actively participate in supporting (social and economic) institutions initiatives aiming to formulate environmentally sustainable policies and solutions. This finding aligns with findings from previous research from [15,39,85], who found a positive relationship between citizens' intentions to reduce single-use plastic consumption and their attitudes towards the issue.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is crucial to acknowledge that desired outcomes from plastic bags' usage reduction can only be achieved when consumers actively participate in supporting (social and economic) institutions initiatives aiming to formulate environmentally sustainable policies and solutions. This finding aligns with findings from previous research from [15,39,85], who found a positive relationship between citizens' intentions to reduce single-use plastic consumption and their attitudes towards the issue.…”
Section: Discussionsupporting
confidence: 91%
“…Typical demarketing tactics and/or instruments, according to [14] include education, prevention, protection, and prosecution. Researchers like [15] urge an earnest need for authorities, businesses, and non-governmental organizations to work together to educate people about the value of environmental and public health protection to prevent detrimental social (including consumer) behaviors to make societies green, healthy, and pluralistic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ek and Soderholm (2010) pointed out that the energy-related activities of household members are important in the policies. Akyıldız and Koçoğlu (2022) showed the relation among attitude toward reducing the use of plastic bags, environmental manner and environmental behaviour. Tehci (2022) studied concerns, knowledge, attitudes, and behaviours of individuals towards marine pollution.…”
Section: Introductionmentioning
confidence: 99%